Green Marketing and Consumer Responses: Examining Purchase Decisions in the Indonesian Skincare Industry - Istanti, Fredianaika; Soliha, Euis (Politeknik Negeri Bandung, 2025)
Evolving trends in beauty and cosmetics production have contributed to environmentally related waste, prompting the need for businesses to uphold ecological integrity. In response, many firms within the cosmetics sector are transitioning toward more environmentally sustainable business models. This study explores green marketing motivation alongside product and brand image relations, analyzing the impact of brand image as a mediating factor in the relationship between green marketing, product quality, and purchase decisions. This study employed PLS-SEM to analyze data collected from 256 respondents who actively use local skincare brands in Indonesia. The sample size was determined based on recommended minimum sample size for PLS-SEM, ensuring adequacy for robust statistical analysis. The findings highlight the pivotal role of brand image as a mediating variable linking green marketing and product quality to consumer purchasing decisions. While green marketing and product quality exert limited direct effects on purchase behavior, both significantly strengthen brand image, which subsequently serves as a critical driver of consumer decision-making. This underscores that firms seeking to convert their green marketing and quality initiatives into actual consumer purchases should prioritize strengthening brand image. Theoretically, the results enrich the understanding of how brand image functions as a strategic link between sustainable marketing efforts and consumer decision-making.